Structure of nods in conversation - Taiga Mori; Yasuharu Den; Kristiina Jokinen (PLoS ONE, 2025)
Head nods are a commonly observed gesture in daily conversations and has attracted the interest of many researchers in human, social, and computer sciences since early studies. However, there has been little research focusing on the structure of nod movement, which sometimes involve repetition of upward and downward movements. In this study, we shed light on this structure of nods which has been previously overlooked. Prior to the analysis, we propose systematic conceptualization of nod movement. First, we define a cycle as a consecutive upward and downward movement as the basic unit of analysis. We next define the number of cycles within a nod as its length and the relative position of a cycle within a nod as its position. We then define the magnitude as the difference between the lowest and highest points of the head within a cycle. In the analysis, we demonstrate that this magnitude varies depending on length and position, thereby providing evidence that nods exhibit a structured pattern. Specifically, three structural patterns were observed: (1) the magnitude of the first cycles increases with length (anticipatory rising), (2) the magnitude decreases proportionally with position (declination), and (3) the magnitude of the final cycles is noticeably smaller than predicted from the preceding trend (final lowering). Finally, we discuss the similarities between the discovered structure and the phonological structure of utterances, suggesting that these structures may represent a universal characteristic of human repetitive actions.